Assessing Building Information Modelling (BIM) Maturity Level in Design and Build Public Projects: Case Studies of Public Projects in Malaysia - Yusoff, Seri Nanisa Sima; Brahim, Juliana; Mohd Nordin, Rumaizah; Preece, Christopher (International Journal of Sustainable Construction Engineering and Technology, 2023)
Design and Build (D&B) is one of the most common project delivery methods to incorporate with Building Information Modelling (BIM) and has brought to light many innovative benefits, including collaboration and integration of work processes. However, there is still confusion and a lack of empirical evidence in the construction industry regarding the interpretation of success in a BIM implementation, especially in D&B projects. Hence, this paper is aimed to assess the current maturity level of BIM in D&B BIM projects. A quantitative method by means of a survey via questionnaire has been used by adopting the "Migration Path Model of BIM for Construction Professionals" to 31 respondents in three (3) public D&B projects. The findings revealed that the implementation of BIM in those three (3) selected projects does not meet the requirement of BIM maturity in projects. Nevertheless, the BIM competencies of the projects gradually increase throughout the shift of project years. The low level of BIM maturity implies a need to have a standardised policy and guideline in determining the maturity and competencies of BIM implementation in projects at the national and market levels. Thus, it is expected that the results of this research will assist in ensuring the benefit of disruptive technology like BIM could be reaped by the construction industry.